Juniper & thorn eaudiobook A novel. - Reid, Ava (HarperAudio, 2022)
From highly acclaimed, bestselling author Ava Reid comes a gothic horror retelling of The Juniper Tree, set in another time and place within the world of The Wolf and the Woodsman, where a young witch seeks to discover her identity and escape the domination of her abusive wizard father, perfect for fans of Shirley Jackson and Catherynne M. Valente. A gruesome curse. A city in upheaval. A monster with unquenchable appetites. Marlinchen and her two sisters live with their wizard father in a city shifting from magic to industry. As Oblya's last true witches, she and her sisters are little more than a tourist trap as they treat their clients with archaic remedies and beguile them with nostalgic charm. Marlinchen spends her days divining secrets in exchange for rubles and trying to placate her tyrannical, xenophobic father, who keeps his daughters sequestered from the outside world. But at night, Marlinchen and her sisters sneak out to enjoy the city's amenities and revel in its thrills, particularly the recently established ballet theater, where Marlinchen meets a dancer who quickly captures her heart. As Marlinchen's late-night trysts grow more fervent and frequent, so does the threat of her father's rage and magic. And while Oblya flourishes with culture and bustles with enterprise, a monster lurks in its midst, borne of intolerance and resentment and suffused with old-world power. Caught between history and progress and blood and desire, Marlinchen must draw upon her own magic to keep her city safe and find her place within it.